The Effect of Live Yeast and Yeast Extracts on Antimicrobial Susceptibilities of Fecal Escherichia coli of Nursery Pigs Weaned from Sows Fed Diets with or without Yeast Additives - Jenna A. Chance; Jordan T. Gebhardt; Joel M DeRouchey; R. G. Amachawadi; V. Ishengoma; T. G. Nagaraja; M. D. Tokach; Jason C. Woodworth; Robert D. Goodband; Qing Kang; Joseph A. Loughmiller (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 340 weaned pigs (Line 241 × 600, DNA; initially 11.2 lb BW) were used in a 45-d study to evaluate previous sow treatment (control vs. yeast additives) and nursery diets with or without added yeast-based pre- and probiotics (Phileo by Lesaffre, Milwaukee, WI) on antimicrobial resistance (AMR) patterns of fecalEscherichia coli. At placement in the nursery, pigs were housed by pen based on sow treatment and randomly assigned to 1 of 2 dietary treatments with 5 pigs per pen and 17 pens per treatment. Treatments were arranged in a 2 × 2 factorial with main effects of sow treatment (control vs. yeast-based pre- and probiotic diet; 0.10% ActiSaf Sc 47 HR+ and 0.025% SafMannan) and nursery treatment (control vs. yeast-based pre- and probiotic diet; 0.10% ActiSaf Sc 47 HR+, 0.05% SafMannan, and 0.05% NucleoSaf from d 0 to 7, then concentrations were lowered by 50% from d 7 to 24). All pigs were fed a common diet from d 24 to 45 post-weaning. TheE. coliwas isolated from fecal samples and species confirmation was accomplished by PCR detection ofuidAandclpBgenes. Microbroth dilution method (Sensititre CMV3AGNF panel plates) was used to determine the minimum inhibitory concentrations (MIC) ofE. coliisolates to 14 different antimicrobials. Isolates were categorized as either susceptible, intermediate, or resistant based on Clinical and Laboratory Standards Institute guidelines. A three-way interaction of sow treatment × nursery treatment × sampling day was observed (P<0.05) for ciprofloxacin, gentamicin, sulfisoxazole, and trimethoprim/ sulfamethoxazole. FecalE. coliisolated from pigs of the yeast-supplemented sow group had increased (P= 0.034) MIC to nalidixic acid and a tendency for increased MIC to ciprofloxacin (P= 0.065) and gentamicin (P= 0.054). Yet, when yeast additives were fed in the nursery there was reduced (P<0.05) fecalE. coliAMR to azithromycin and chloramphenicol. All fecalE. coliisolates were considered susceptible to all antimicrobials, except tetracycline on d 5. In conclusion, feeding sows live yeast and yeast extracts could potentially impact fecalE. coliAMR in their progeny. Furthermore, feeding live yeast and yeast additives in the nursery may alleviate the AMR of azithromycin and chloramphenicol ofE. coliisolated from nursery pig fecal material.
Keywords: E. coli; nursery pig; probiotics; yeast; yeast extracts